Pre-screening systems for early disease prediction, detection, and prevention - Edoh, Thierry Oscar, 1968-; Pawar, Pravin, 1978-; Mohammad, Sagar, 1975- (Advances in medical diagnosis, treatment, and care (AMDTC) book series., 2019)
"This book focuses on using non-invasive biomedical sensor devices, IOT solutions, and knowledge database solutions for pre-screening of diseases so that the risk of disease is reduced, or it can be detected early enough to treat the disease most effectively"--Provided by publisher